UJI KUAT TEKAN BETON PADA MATERIAL ALAM PASIR PANTAI MUARA LAPAO-PAO - Muhammad Buttomi Masgode; Arman Hidayat; Rusli Rusli (LPPM, 2023)
The research on the use of sea sand as a fine aggregate in the manufacture of concrete is motivated by the beach sand of Muara Lapao Pao. to meet material needs in the estuary area of ​​Lapao Pao and its surroundings. This study aims to determine how much compressive strength the concrete produces when using sand from Muara Lapo Pao beach. The compressive strength of concrete is planned f'c 18 MPa. Cylindrical concrete samples totaled 18 pieces. The results of this study indicate that the compressive strength of concrete produced using Muara Lapao Pao beach sand without treatment is higher than Muara Lapao Pao beach sand with washing treatment. The compressive strength of concrete using Muara Lapao-pao beach sand without treatment with a curing age of 7, 14 and 28 days with a design quality of 18 MPa, namely 13.04 Mpa, 16.56 Mpa and 21.23 Mpa. Compared to the Lapao-pao Muara sand with washing treatment with a treatment age of 7, 14, and 28 days with a design quality of 18 MPa, namely 15.29 MPa, 16.65 MPa, and 16.84 MPa. With a percentage increase in concrete compressive strength of 24.38% of the design compressive strength for unwashed beach sand conditions.